Human Parechovirus 3 in Infants: Expanding Our Knowledge of Adverse Outcomes. Issue 1 (January 2019) - Joseph, Lindsay; May, Meryta; Thomas, Marion; Smerdon, Carla; Tozer, Sarah; Bialasiewicz, Seweryn; McKenna, Ronan; Sargent, Philip; Kynaston, Anne; Heney, Claire; Clark, Julia E.
Abstract : Background: Human parechovirus particularly genotype 3 (HPeV3) is an emerging infection affecting predominantly young infants. The potential for neurologic sequelae in a vulnerable subset is increasingly apparent. A review of 2 epidemics of human parechovirus (HpeV) infection in 2013 and in 2015 in Queensland, Australia, was undertaken, with an emphasis on identifying adverse neurodevelopmental outcome. Methods: All hospitalized cases with laboratory-confirmed HPeV infection between October 2013 June 2016 were identified. Clinical, demographic, laboratory and imaging data were collected and correlated with reported developmental outcome. Results: Laboratory-confirmed HPeV infections were identified in 202 patients across 25 hospitals; 86.6% (n = 175) were younger than 3 months 16.3% (n = 33) received intensive care admission. Of 142 cerebrospinal fluid samples which were HPeV polymerase chain reaction positive, all 89 isolates successfully genotyped were HPeV3. Clinical information was available for 145 children; 53.1% (n = 77) had follow-up from a pediatrician, of whom 14% (n = 11) had neurodevelopmental sequelae, ranging from hypotonia and gross motor delay to spastic quadriplegic cerebral palsy and cortical visual impairment. Of 15 children with initially abnormal brain magnetic resonance imaging, 47% (n = 7) had neurodevelopmental concerns, the remainder had normal development at follow-up between 6 and 15 months of age. Conclusions: This is the largest cohort of HPeV3 cases with clinical data and pediatrician-assessed neurodevelopmental follow-up to date. Developmental concerns were identified in 11 children at early follow-up. Abnormal magnetic resonance imaging during acute infection did not specifically predict poor neurodevelopmental in short-term follow-up. Continued follow-up of infants and further imaging correlation is needed to explore predictors of long-term morbidity. Abstract : Supplemental Digital Content is available in the text.